1984
DOI: 10.1002/hlca.19840670731
|View full text |Cite
|
Sign up to set email alerts
|

Photoreaction of (RS,SR)‐3‐Phenyl‐6‐hepten‐2‐ol. Benzene‐Olefin Cycloadditions as a Synthetic Route to [5.5.5.5] Fenestranes. Part III

Abstract: SummaryIrradiation of (RS,SR)-3-Phenyl-6-hepten-2-01 (3n) gave the photoproducts 6n-10n. Some reactions of 6n and 8n are reported. The regio-and diastereoselectivity observed in the photoreaction of substituted 5-phenylpentenes is discussed with respect to conformational preferences of the compounds to be irradiated.Introduction. -Polycyclic hydrocarbons in which four rings are annulated in such a way that they share a common C-atom are of interest for a study of the planarization of the tetracoordinate C-atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…[1] In particular, WenderЈs group has used the reaction for the synthesis of polyquinanes, [2] while Keese and co-workers have used it to prepare fenestranes. [3] The synthetic potential of the reaction is demonstrated by the photochemical behaviour of 5-phenylpent-1-ene and of 5-(2-methoxyphenyl)pent-1-ene (Scheme 1). Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In particular, WenderЈs group has used the reaction for the synthesis of polyquinanes, [2] while Keese and co-workers have used it to prepare fenestranes. [3] The synthetic potential of the reaction is demonstrated by the photochemical behaviour of 5-phenylpent-1-ene and of 5-(2-methoxyphenyl)pent-1-ene (Scheme 1). Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…Photochemical cycloaddition of benzene derivatives toward several types of alkenes has been extensively studied, and 2 + 2, 3 + 2, and 4 + 2 cycloadditions were reported. The reaction has received much attention from both mechanistic and synthetic perspectives because it is also a useful method of synthesizing natural products. On the other hand, while the valence isomerization of azaaromatic compounds, such as pyridines, was reported three decades ago, only a few reports for the photochemical cycloaddition with alkenes are known. New developments in the ring transformation of heteroaromatics will result in useful synthetic methodology of heterocyclic compounds . Recently, we found that introduction of both electron-donating and -withdrawing substituents to the pyridine ring shows high reactivity toward dimerization and addition reaction.
1
…”
Section: Introductionmentioning
confidence: 99%